2022
DOI: 10.17323/jle.2022.12537
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Process-genre Approach on Learners’ Academic Writing and Higher Order Thinking Skills

Abstract: Background. The study of using process-genre approach that was used to increase the writing competence had been conducted by many researchers. However, the contirbution of this learning approach for HOTs aspects has not been done by many researchers, especially on learning writing Indonesian Purpose. Many studies only focused on one research approach, consequently, the finding was not quite comprehensive. Besides, to examine the effect of process-genre approach on academic writing competence and HOTs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Numerous studies were conducted on self-efficacy (SE), and how the genre-based approach (GBA) enhanced academic writing was explained, while the current study primarily explored the characteristics of self-efficacy (SE) and motivation (Wardhana, 2022). The results showed that the genre-based approach (GBA) improved academic writing proficiency and self-efficacy (SE), therefore, the current study perpetuated this suggestion.…”
Section: Research Papersmentioning
confidence: 83%
“…Numerous studies were conducted on self-efficacy (SE), and how the genre-based approach (GBA) enhanced academic writing was explained, while the current study primarily explored the characteristics of self-efficacy (SE) and motivation (Wardhana, 2022). The results showed that the genre-based approach (GBA) improved academic writing proficiency and self-efficacy (SE), therefore, the current study perpetuated this suggestion.…”
Section: Research Papersmentioning
confidence: 83%
“…Universal journal of educational research [26] Pen-and-paper or online? An academic writing course to teachertrainees Cogent education [27] Process genre approach to L2 academic writing: An intervention study XLinguae [28] Reflections on employing innovative approaches in an academic writing course PONTE international scientific researchs journal [29] Analysing a faculty learning community strategy based on a process-genre approach supported by videos to develop the writing competence of English teaching students DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada [30] A process-genre approach to teaching writing report text to senior high school students Indonesian journal of applied linguistics [31] A pre-experimental study on a process-genre approach for teaching essay writing Journal of language & education [32] Pre-writing and post-writing explicit instruction: Differential effects on L2 learners' writing accuracy RELC journal [33] Impacts of process-genre approach on EFL sophomores' writing performance, writing self-efficacy, writing autonomy Journal of language & education [34] Exploring the impact of process-genre approach on learners' academic writing and higher order thinking skills Journal of language & education [35] Explicit instruction in an EFL writing class: A process-genre perspective Linguistics research [36] Bringing innovation to EFL writing: The case of a primary school in Hong Kong…”
Section: Titlementioning
confidence: 99%
“…Figure 8 is shown below to show the frequency of dependent variables researched. PhD English academic writing skills; Feasibility of the approach for a doctoral EAP program [25] Asian EFL pre-university students' writing performance; Writing quality; Learners' engagement [26] Needs of university students and lecturers in writing instructions [27] Effectiveness of a writing course; Senior ELT students' writings in pen-and-paper (portfolio) work and online work [28] Master degree program's students' academic writing skills; Students' perceptions [29] Challenges faced by the lecturer of an academic writing course for pre-service EFL teachers [30] Writing competence in an English Teaching Program from the trainee English teachers/students' perspectives [31] Senior high students' writing skills of report text [32] Undergraduate students' EFL academic essay writing; Students' perceptions [33] College students/L2 learners' overall writing accuracy and errors [34] Vietnamese university EFL students' writing performance, self-efficacy and autonomy [35] University students' academic writing competence on HOTs, students' attitudes and expectations on their learning experience [36] University students' writing improvement [37] Primary school EFL teachers' incorporation of focus on writing program; Primary school students' writing performance; Factors facilitating change in the writing classroom; Challenges teachers face [38] Undergraduate students' individual writing performances; Levels of the cognitive load [39] College L2 students' perceived metacognitive strategy; Students extent of metacognitive strategies deployment…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…This nature-inspired language scholars formulate approaches (process-based approach, process-genre approach) that pass through various stages such as the construction of the context, examination of the text of the model, collective construction of the text, individual construction of the text, and contemplation on prose. Also, Zhao (2017) in Wardhana (2022) suggested the following stages exploration of intent and functions, language scaffolding, modeling, mutual/ joint text construction, unique text construction, and description. Learners' active involvement and knowledge discovery in the learning process play a significant role.…”
Section: Literature Reviewmentioning
confidence: 99%